A study of dynamic plasticity in austenite stainless steels with a gradient distribution of nanoscale twins. (May 2017) - Zhu, Linli; Wen, Chunsheng; Gao, Chongyang; Guo, Xiang; Lu, Jian
Abstract: The dynamic plastic behavior related to the gradient distribution of twin spacing in 304 stainless steel thin wires is investigated experimentally with the strain rate varying from 1 × 10 − 3 /s to 1.5 × 10 4 /s. Such gradient-nanotwinned structures are prepared by surface mechanical attrition treatment. A mechanism-based dynamic plastic model is developed to describe the strain-rate dependent stress-strain response in gradient-nanotwinned austenite stainless steels. A good agreement between experimental data and simulations was achieved, and further theoretical predictions demonstrated that the dynamic plastic behavior is sensitive to the twin spacing and volume fraction of gradient-nanotwinned region in austenite stainless steel wires. Graphical abstract: